Analisis Strata Norma Pada Puisi Elegi Sampah Karya Sri Setianingsih - Umar, Umar; Putri, Nina Queena Hadi; Agustian, Jaka Farih (Adjektiva: Educational Languages and Literature Studies, 2021)
This study aims to describe the strata (layers) of norms contained in the Elegi Sampah Garbage by Sri Setianingsih. The method used in this research is descriptive, while the approach used is a structural approach, namely an approach that trying to understand poetry from the elements inherent in poetry in the form of layers of norms in a poem poetry creation. Sources of data taken through the poetry anthology book Sajak Cermin by Sri Setianingsih entitled Elegi Sampah. The data analysis technique in this research is the content analysis. This technique tries to analyze documents to find out their contents and meanings contained in the document. Based on the results of research and discussion, it can be concluded that the result is to discuss the various strata (layers) of norms that contained in the poem Elegi Sampah by Sri Setianingsih. The strata (layers) of norms discussed These are the sound layer, the meaning layer, the object layer, the world layer and the metaphysical layer.